농업용수 관리체계 개편의 방향과 정책과제 - 김홍상 (한국농촌경제연구원, 2004)
The purpose of this research is to suggest the policy issues and directions of reorganizing the agricultural water management systems(AWMS). Especially, it focuses at the way to unify two separated irrigation water managers to relieve farmers' complaints about inequality of cost-payment and to resolve problems occurred by the separated management system. To address this purpose, this research overviews the current situations and problems of AWMS and new trends and changes in agricultural water management. Significant problems of AWMS can be summarized into five ones as follows; (1) inequality in paying management cost, (2) lack of farmers' participation in irrigation water management, (3) increasing government subsidy and unstable financial source, (4) difficulties of integrated management owing to separated management systems, (5) overall deterioration of irrigation facilities. As those problems have gotten more serious, agricultural or rural issues have changed tremendously. Especially, recent rapid urbanization and industrialization have resulted in an increased water demand for various sectors like municipal, industrial, intensive farming, and environment-friendly farming etc. and urge the value of irrigation water in the point of view of environment, safety, landscape to be reevaluated. Based on the above, the basic directions of reorganizing AWMS can be introduced as follows. (1) an integrated management system based on watershed to improve equality in water use which is degraded by separated management systems, (2)　a participatory management system with farmers, local authorities and people, (３）a social allocation system based on the benefit(user-pay) principle and considered on public value of agricultural water and irrigation facilities. Under these directions, we can consider three ways as feasible measures to reorganize AWMS in brief. One is the way to unify two separated AWMSs and another is to establish the third organization as a new local manager. The other is to keep today's AWMS and fix its problems gradually. The first one is analyzed as the reorganized system with the results of survey that most of stake-holders such as government, KARICO, local authorities and farmers preferred to unifying AWMS into KARICO(Korea Agricultural and Rural Infrastructure Corporation). In order to unify AWMS into KARICO and reorganize it as efficient and effective AWMS, these policy issues should be considered; (1) to enlarge the opportunities for farmers and local people to participate in agricultural water management, (2) to take some financial measures to cover additional management cost, (3) to prepare legal and institutional vehicles to compensate private facilities, land and so on, (4) to improve specialty as a management expertise, (5) to survey all the irrigation facilities around the country completely and to modernize outdated irrigation facilities. Researcher : Kim Hong-Sang, Shin Eun-Jung E-mail : hskim@krei.re.kr